2014
DOI: 10.1371/journal.pone.0100669
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for Lysyl Oxidase in Pluripotent Mesenchymal Cell Proliferation and Relevance to Inflammation-Associated Osteopenia

Abstract: Lysyl oxidase is a multifunctional enzyme required for collagen biosynthesis. Various growth factors regulate lysyl oxidase during osteoblast differentiation, subject to modulation by cytokines such as TNF-α in inflammatory osteopenic disorders including diabetic bone disease. Canonical Wnt signaling promotes osteoblast development. Here we investigated the effect of Wnt3a and TNF-α on lysyl oxidase expression in pluripotent C3H10T1/2 cells, bone marrow stromal cells, and committed osteoblasts. Lysyl oxidase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…We compared mRNA expression array profiles between Sca‐1‐high S1 cells and Sca‐1‐negative S1 cells and identified 85 genes overexpressed by > 1.5‐fold in S1M cells ( Sca‐1 signature ) (Supporting Information Table S3). The Sca‐1 signature included a Wnt ligand, wnt7a, and Wnt positive regulators, such as Nestin , PRRX1 , and TNC , and putative Wnt target genes, such as LOX , Ifitm3 , and Lipocalin2 . Thus, the microarray data indicated the transcriptional activation of the Wnt signaling pathway in Sca‐1 high cells.…”
Section: Resultsmentioning
confidence: 95%
“…We compared mRNA expression array profiles between Sca‐1‐high S1 cells and Sca‐1‐negative S1 cells and identified 85 genes overexpressed by > 1.5‐fold in S1M cells ( Sca‐1 signature ) (Supporting Information Table S3). The Sca‐1 signature included a Wnt ligand, wnt7a, and Wnt positive regulators, such as Nestin , PRRX1 , and TNC , and putative Wnt target genes, such as LOX , Ifitm3 , and Lipocalin2 . Thus, the microarray data indicated the transcriptional activation of the Wnt signaling pathway in Sca‐1 high cells.…”
Section: Resultsmentioning
confidence: 95%
“…45 The crosslinking then facilitates callus osteogenesis and provides the necessary framework for bone mineralization. 46 In this work, we proved through the in vitro experiment that 317L-Cu SS has significant effect in enhancing the activity of LOX in hBMSCs. It is possibly because of this that more of the woven fibrous tissue was observed through Masson staining in the early stage of callus formation in the 317L-Cu SS group.…”
mentioning
confidence: 74%
“…Because C3H10T1/2 cells produce little or no extracellular matrix under these conditions, the question was raised regarding LOX function. LOX shRNA studies showed that LOX was required for normal proliferation of C3H10T1/2 cells, and that differentiation into osteoblasts was blocked in cells expressing diminished levels of LOX [74]. Similarly, LOX expression was found to be required for differentiation of C3H10T1/2 cells to adipocytes [75, 76].…”
Section: Lysyl Oxidase Familymentioning
confidence: 99%
“…Decreased OPG and increased CCN2 can each contribute to osteoclast development and fusion [94, 95] which was observed to be increased in the presence of rLOX-PP [92]. The relative contributions and mechanisms of abnormal high levels of active LOX enzyme on the one hand [60, 74, 93], and LOX-PP on the other, to decouple osteoblast and osteoclast interactions in the presence or absence of cancer cells [92] remain to be adequately understood, and are likely to influence bone metastasis. For example, direct injection of the osteolytic prostate cancer PC3 cell line over expressing rLOX-PP into the tibia of mice increased bone destruction compared to PC3 control cells determined by μCT analyses, while injection of DU145 osteogenic cancer cells overexpressing rLOX-PP created osteoblastic lesions that were similar compared to its DU145 control [92].…”
Section: Lysyl Oxidases and Bone Metastasismentioning
confidence: 99%